Effect of fly ash and ball milling time on CNT-FA reinforced aluminium matrix hybrid composites. (10th May 2019) - Udaya,; Fernandes, Peter
Abstract: In this paper, Aluminium metal matrix hybrid composite was fabricated using powder metallurgy, where MWCNT and burnt coal waste (pollutant) used as reinforcing materials. The density and hardness of specimen was calculated and influence of fly ash on them was discussed. It was observed that hardness had increasing effect for certain weight percentage of fly ash( up to 8 wt%) and above that level showed the negative effect on them. An increase of 63.6% in hardness and 107% in compressive strength was observed for the composite compared to pure aluminum. The increased ball milling time resulted in damage of CNT. Compressive strength test revealed that MWCNT along with fly ash addition resulted in the improvement of compressive strength compared to pure Al.